2008
DOI: 10.1021/jm800180e
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel, Orally Active Himbacine-Based Thrombin Receptor Antagonist (SCH 530348) with Potent Antiplatelet Activity

Abstract: The discovery of an exceptionally potent series of thrombin receptor (PAR-1) antagonists based on the natural product himbacine is described. Optimization of this series has led to the discovery of 4 (SCH 530348), a potent, oral antiplatelet agent that is currently undergoing Phase-III clinical trials for acute coronary syndrome (unstable angina/non-ST segment elevation myocardial infarction) and secondary prevention of cardiovascular events in high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
208
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 242 publications
(214 citation statements)
references
References 34 publications
3
208
0
Order By: Relevance
“…In several preclinical studies, blocking of the thrombin receptor protease-activated receptor 1 by several compounds such as vorapaxar and atopaxar was suggested as a promising adjunct therapy. [46][47][48][49] In our study, apelin was found to mainly inhibit thrombin-and collagen-mediated platelet activation ( Figure 7D), suggesting the potential use of this naturally occurring inhibitor (and/or its derivatives) of platelet activation in therapy. In conclusion, we demonstrate in the present work a new biological function of apelin peptide that inhibits platelet activation and aggregation mainly induced by thrombin and collagen.…”
Section: Discussionmentioning
confidence: 63%
“…In several preclinical studies, blocking of the thrombin receptor protease-activated receptor 1 by several compounds such as vorapaxar and atopaxar was suggested as a promising adjunct therapy. [46][47][48][49] In our study, apelin was found to mainly inhibit thrombin-and collagen-mediated platelet activation ( Figure 7D), suggesting the potential use of this naturally occurring inhibitor (and/or its derivatives) of platelet activation in therapy. In conclusion, we demonstrate in the present work a new biological function of apelin peptide that inhibits platelet activation and aggregation mainly induced by thrombin and collagen.…”
Section: Discussionmentioning
confidence: 63%
“…It is an experimental pharmaceutical treatment for acute coronary syndrome as a very powerful platelet inhibitor (21).In January 2011, the clinical trial was www.intechopen.com Antiplatelet Therapy in Cardiovascular Disease -Past, Present and Future 5 halted for patients with stroke and mild heart conditions due to safety reasons. It is unknown if it will continue.…”
Section: Proteasa-activated Receptors Antagonistmentioning
confidence: 99%
“…Later, several laboratories have reported a few series of antagonists obtained from HTS of diverse libraries of non-peptide small molecules, followed by optimization [19,30]. The most advanced of these antagonists is SCH-530348 (named vorapaxar, Figure 1), derived from the natural product himbacine, which currently is undergoing Phase III clinical trials in patients with acute coronary syndrome and in patients with atherosclerosis [31][32][33]. Up to now, there is not structural information on the binding sites of these PAR1 antagonists to be used for structure-based design of new antagonists.…”
Section: Introductionmentioning
confidence: 99%